Late postoperative opacification of a new type hydrophilic acrylic intraocular lens - Jin Xie; Xinyi Zang; Shilan Mao; Jie Sun; Ting Liu; Yunhai Dai (Advances in Ophthalmology Practice and Research, 2023)
Background: To report the clinical consequences and laboratory characteristics of late postoperative opacification of a hydrophilic acrylic intraocular lens (US-860UV IOL) as well as the prognosis of IOL replacement. Methods: Forty medical records (42 eyes) of patients with US-860UV IOL opacification reporting decreased or lost vision who underwent IOL explantation between 2017 and 2019 were reviewed. Explanted IOLs were analyzed by slit-lamp examination, confocal microscopy, scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDS) at the Shandong Key Laboratory of Ophthalmology, Shandong Eye Institute, Shandong First Medical University, and Qingdao University of Science and Technology, Qingdao, China. Results: The mean age of the 40 patients was 74.83 ​± ​7.57 (63–92) years. The mean interval between cataract surgery and diagnosis of opacification was 32.38 ​± ​8.76 (17–48) months. Systemic diseases were found without statistical correlations, the most frequent being arterial hypertension, coronary heart disease, and diabetes mellitus. Visual acuity improved from 1.42 ​± ​1.03 to 0.31 ​± ​0.16 (logMAR) after IOL replacement. SEM, EDS and alizarin red staining showed uniformly distributed, diffuse, milk-white opacification, with calcium and phosphorus deposits on the optic and haptic surfaces that could be dissolved in 1% HCl. Conclusions: Calcium and phosphorus deposition was the main cause of hydrophilic acrylic US-860UV IOL opacification. IOL replacement can safely and effectively improve the visual acuity of patients.